The Relationship between Crude Oil and Coal Markets: A New Approach - Zamani, Narjes (International Journal of Energy Economics and Policy, 2016)
The level of substitutability of crude oil and coal in production and consumption may lead to the relationship between them. In this paper, the relationships between crude oil market and coal market are investigated, using a structural vector autoregressive model (SVAR). We apply the Kilian Index (2009) to distinguish between the effects of oil market demand shocks and global aggregate demand shocks. The empirical results suggest that coal prices are affected by the supply and demand shocks of the oil market, while oil supply shocks have no effect on oil prices. This shows a high level of interaction between the crude oil market and the coal market, arising mainly due to the role of substitution. The effect of global aggregate demand on the price of coal is higher than the effect on the price of oil. Meanwhile, the fear of future oil supply affects the coal market only temporarily. Keywords: Crude oil price, Coal price, Oil supply shock JEL Classifications: Q41, Q43